Implementation of Good Governance Principles in Public Services in Bandar Dua District, Pidie Jaya Regency - Nurliana Nurliana; Badruzzaman Badruzzaman; Muna Warah (Dinasti International Journal of Education Management And Social Science, 2025)
Good governanceis an important concept in the implementation of effective, transparent, and accountable governance. This study aims to analyze the application of good governance principles in public services in Bandar Dua District, Pidie Jaya Regency, with a focus on participation, transparency, responsibility, and completeness of infrastructure. The research method uses a qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the application of good governance principles still faces several challenges, such as lack of community participation, obstacles to information transparency, limited infrastructure, and less than optimal responsibility. This article provides recommendations for improving the quality of public services by strengthening community participation, increasing transparency, and improving infrastructure.